Analysis of Wind Energy Potential and Optimum Wind Blade Design for Jamshoro Wind Corridor - SYED UMAID ALI (Mehran University Research Journal of Engineering and Technology, 2017)
Pakistan is facing energy crisis since last decade. This crisis can be effectively handled by utilizing alternative energy resources. Pakistan has a huge wind energy potential of about 50,000MW. The contribution of costal area of Sindh, Pakistan in the total wind energy potential is about 43000MW. The Jamshoro wind corridor has the highest wind potential of all coastal areas of Sindh. In this paper a wind blade design has been developed and optimized for Jamshoro wind corridor. The theoretical blade design include the airfoil selection, appropriate chord length selection and optimization of twist angle. The designed blade has been analyzed using Q-blade. Considering the Jamshorowind conditions, blade of around 43 meters have been designed and optimized theoretically. Then the theoretical design is also been checked and verified in Q-blade. Theoretical optimization includes using different combinations of NACA profiles and using exhaustive iterative method to get optimized twist angle. This ensures the design with maximum power output with respect to wind speed of Jamshoro. For low wind speeds, theoretical results and simulated results in Q-blade were almost same but for high wind speeds, results were significantly different due to limitation of iterations in theoretical design